Comportamiento asertivo y relación interpersonales en estudiantes del quinto y sexto grado de educación primaria Institución Educativa Señor de los Milagros N° 60259 San Antonio distrito de San Pablo Bajo Amazonas 2025 - Mora López, Javier (2025)
The study's general objective is to relate assertive behavior with interpersonal relationships among fifth- and sixth-grade students at the Señor de los Milagros Educational Institution No. 60259, San Antonio, San Pablo Bajo Amazonas District, 2025. The research was conducted using a descriptive, quantitative approach and a correlational, cross-sectional design. The sample was identical to the population, comprising 63 students in fifth and sixth grade. A questionnaire was used to collect data for the assertive behavior variable, and a Likert-type scale was used for the interpersonal relationships variable. The overall result was a Pearson correlation coefficient of rxy = 0.784, indicating a strong, direct, positive relationship. The study concluded this suggests that Assertive Behavior is related to Interpersonal Relationships.